Analysis of social stress, sleep quality, and sodium on hypertension in West Sinjai - Oruh, Shermina; Agustang, Andi; Ilyas, Magfirah; Ibrahim, Irviani Anwar (Universitas Islam Negeri Alauddin Makassar, 2024)
Social stress can trigger activation of the autonomic nervous system, which can increase blood pressure. The body's reaction to stress can include the release of stress hormones, such as cortisol, which can affect cardiovascular function. Individuals who experience social stress may tend to adopt unhealthy lifestyles, such as poor eating habits and poor sleep quality. Hypertension is an increase in systolic blood pressure more than equal to 140 mmHg and diastolic more than equal to 90 mmHg. Hypertension or high blood pressure is a medical condition that significantly increases the risk of heart, brain, kidney and other diseases. This study aims to see the relationship between stress with the incidence of hypertension in the working area of the Manipi Health Center, Sinjai Barat District. The type of research used is quantitative research with an analytic observational approach with a cross sectional study design. The sampling technique used is non-probability sampling using purposive sampling, with a total sample of 95 people. The results of this study indicate that factors associated with the incidence of hypertension, namely social stress with a p-value of 0.000 (<0.05), sleep quality with a p-value of 0.033 (<0.05), sodium intake with a p-value of 0.022 (<0.05). By understanding the complex relationship between social stress, sleep quality and sodium intake with hypertension, more effective intervention strategies can be designed to reduce the risk and manage the negative health impacts that may arise from social stress. It also provides a foundation for health promotion that focuses on overall social and psychological well-being